The broiler chicken industry in Malaysia: some evidences on the structure, conduct and performance - Kaur, Bisant; Mohamed Arshad, Fatimah (Federal Agricultural Marketing Authority (FAMA), 2008)
The broiler chicken industry in Peninsular Malaysia has undergone major structural changes in recent years, notably the increasing vertical integration in the industry, which has led to concerns over market power by wholesalers at the expense of producers and consumers. This paper investigates the performance of the broiler market by applying the structure, conduct and performance approach. Using primary data collected from a survey on the wholesale market for broilers, it was found that there was a high degree of concentration in most of the wholesale markets as evident by high concentration ratio and Herfindahl-Hirshman Index. There are also several conditions that restrict the entry of new players. However, in spite of structural rigidities, the study found evidence of spatial market integration using cointegration analysis. This finding suggests that the government could reconsider price control policy measures in the market.